Ecopsychosocial Interventions in Cognitive Decline and Dementia: A New Terminology and a New Paradigm. (September 2016) - Zeisel, John; Reisberg, Barry; Whitehouse, Peter; Woods, Robert; Verheul, Ad
Dementia is a major medical and social scourge. Neither pharmacological nor nonpharmacological interventions and treatments have received sufficient funding to be meaningful in combatting this tsunami. Because the term—"nonpharmacological"—refers to what these interventions are not, rather than what they are, nonpharmacological treatments face a special set of challenges to be recognized, accepted, funded, and implemented. In some ways, the current situation is analogous to using the term "nonhate" to mean "love." This article presents a carefully reasoned argument for using the terminology "ecopsychosocial" to describe the full range of approaches and interventions that fall into this category. These include interventions such as educational efforts with care partners, social support programs for individuals with various levels of dementia, efforts to improve community awareness of dementia, an intergenerational school where persons with dementia teach young children, and the design of residential and community settings that improve functioning and can reduce behavioral symptoms of dementia. The proposed terminology relates to the nature of the interventions themselves, rather than their outcomes, and reflects the broadest range of interventions possible under the present rubric—nonpharmacological. The goal of this new label is to be better able to compare interventions and their outcomes and to be able to see the connections between data sets presently not seen as fitting together, thereby encouraging greater focus on developing new ecopsychosocial interventions and approaches that can improve the lives of those with dementia, their care partners, and the broader society.